Rancang Bangun Aplikasi Administrasi Kepegawaian Pada PT Perkebunan Nusantara XII (Persero) Surabaya - Hendrawan, Agus; Sudarmaningtyas, Pantjawati; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Perkebunan Nusantara is government enterprise that entirely owned by republic of Indonesia. Employee data registration process need employee curriculum vitae and wages classification of each employee to complete the process. The problem that occurs because of rank difference between the director offices, regional offices and gardens. For example, employee a working in gardens and their rank is IIIB/2, then the director office promote the employee into IIIB/3 rank. The promotion approval will be send to the gardens employee a currently working, however the approval still yet to arrive, this causing the employee data obsolete. The director office will only pay the salaries according to the employee data, however because of obsolete data, the director office pay the wrong amount of salaries for employee A. This also cause gardens side and regional office side didn`t know the number of employee that entering their retirement age and the number of retired employee. Based upon the problem PTPN XII currently faced, application that capable to manage employee data in real time and integrated are greatly needed. This application can produce information that ease regional office and gardens to know the number of employee that entering their retirement age and retired employee.